2009
DOI: 10.1158/0008-5472.can-08-3232
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Induction of EphB4 over EphB2 and Its Implication in Colorectal Cancer Progression

Abstract: The receptor tyrosine kinase EphB2 is expressed by colon progenitor cells; however, only 39% of colorectal tumors express EphB2 and expression levels decline with disease progression. Conversely, EphB4 is absent in normal colon but is expressed in all 102 colorectal cancer specimens analyzed, and its expression level correlates with higher tumor stage and grade. Both EphB4 and EphB2 are regulated by the Wnt pathway, the activation of which is critically required for the progression of colorectal cancer. Differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
144
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 25 publications
9
144
0
Order By: Relevance
“…This was an attractive hypothesis given that most human tumors express EphB4 (17)(18)(19)(20) and that distinct endothelial cell populations express ephrinB2 on their luminal aspect (28). Likewise, it has recently been reported that tumor cell-expressed EphB4 promotes metastatic dissemination (40). Combining cellular experiments with sensitive luciferase-based in vivo cell trafficking assays, we show in the present study that (a) the extracellular domain of EphB4 expressed by tumor cells and the extracellular domain of ephrinB2 expressed by endothelial cells is sufficient to mediate rapid and stable adhesion between tumor cells and endothelial cells, (b) the extracellular domain of EphB4 is sufficient to mediate enhanced tumor cell migration, (c) full-length tumor cell expressed EphB4, but not signaling incompetent cytoplasmically truncated ΔC-EphB4 is capable of mediating preferential trafficking of tumor cells to the lungs, the liver, and the kidneys, but not to the similarly well-perfused heart, (d) lung endothelial cells, but not heart endothelial cells, express ephrinB2, and (e) the preferential EphB4-mediated trafficking of EphB4-expressing tumor cells can be blocked by treatment with soluble EphB4-Fc given prior to tumor cell injection.…”
Section: Discussionmentioning
confidence: 99%
“…This was an attractive hypothesis given that most human tumors express EphB4 (17)(18)(19)(20) and that distinct endothelial cell populations express ephrinB2 on their luminal aspect (28). Likewise, it has recently been reported that tumor cell-expressed EphB4 promotes metastatic dissemination (40). Combining cellular experiments with sensitive luciferase-based in vivo cell trafficking assays, we show in the present study that (a) the extracellular domain of EphB4 expressed by tumor cells and the extracellular domain of ephrinB2 expressed by endothelial cells is sufficient to mediate rapid and stable adhesion between tumor cells and endothelial cells, (b) the extracellular domain of EphB4 is sufficient to mediate enhanced tumor cell migration, (c) full-length tumor cell expressed EphB4, but not signaling incompetent cytoplasmically truncated ΔC-EphB4 is capable of mediating preferential trafficking of tumor cells to the lungs, the liver, and the kidneys, but not to the similarly well-perfused heart, (d) lung endothelial cells, but not heart endothelial cells, express ephrinB2, and (e) the preferential EphB4-mediated trafficking of EphB4-expressing tumor cells can be blocked by treatment with soluble EphB4-Fc given prior to tumor cell injection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, down-regulation of EphB4 also resulted in a reduction in the microvessel density of tumours suggesting a negative effect on ephrin-B2 reverse signalling due to the absence of EphB4 [141]. The same findings were also concluded for studies in breast cancer cells [127], ovarian cancer cells [123,142], colorectal cancer cells [143] and bladder cancer cells [144]. These results were also demonstrated in murine mammary and ovarian xenograft models [15], and compared to models that over-expressed EphB4 which showed accelerated tumour progression and increased lung metastasis [145].…”
supporting
confidence: 69%
“…T-ALL cells, however, often develop immunoevasive properties and protect themselves from the cytotoxic action of allogeneic lymphocytes (17,21). Because Eph receptors have been shown to initiate antiapoptotic responses in nonlymphoid malignancies (25)(26)(27)(28)(29)(30), we examined the ability of EphB receptors to interfere with FasR-initiated cell death in malignant T cells. To assess the effect of EphBs, we stimulated H9 and Molt-16 cells with the activating anti-FasR Ab, 7C11, alone or in the presence of increasing concentrations of the common ligand for EphB3 and EphB6, ephrin-B2 (34,38).…”
Section: Ephb Receptors Are Expressed By Malignant T Cells and Protecmentioning
confidence: 99%
“…Accumulating observations show that tyrosine kinase receptors of the Eph family are involved in the regulation of cell survival in nonhematopoietic malignancies, including the antiapoptotic action of the EphA2 receptor in breast cancer (25) and of the EphB4 receptor in colorectal cancer (26), ovarian cancer (27), head and neck carcinoma (28), mesothelioma (29), and prostate cancer (30), indirectly suggesting that proteins of the Eph group may also provide protection for malignant lymphocytes; however, little is known about the role of Eph receptors in leukemias and lymphomas.…”
mentioning
confidence: 99%